Huge Hepatic Spontaneous Sub-Capsular Hematoma: A Case Report - Zarghami, Anita; Tajik, Alireza; Ahmadi, Samaneh (Novelty in Biomedicine, 2024)
Background: Hepatic spontaneous sub-capsular hematoma is uncommon. This is a life-threatening condition because the rupture of this hematoma is accompanied by uncontrolled intra-abdominal hemorrhage. Cases Report: We presented a 71-year-old man with a huge hepatic sub-capsular hematoma without any history of trauma or coagulopathy. The patient received heparin due to a neglected myocardial infarction. Blood pressure and hemoglobin levels decreased. The drug was discontinued, an abdominal computed tomography (CT) scan was done for him, and a huge hepatic sub-capsular hematoma was detected. Conclusion: Spontaneous liver subcapsular hematoma may be found in patients with a history of surgery on the liver site and those with a history of COVID-19. In these patients, hemodynamic instability should increase the doubt of physicians about a rupture of hepatic hematoma.